PERBAIKAN GANGGUAN METABOLIK BALITA STUNTING PASCA SUPLEMENTASI ASAM AMINO SISTEIN DI WILAYAH KERJA PUSKESMAS PACERAKKANG - Hendrayati, Hendrayati; Titi, ZA, A. Toewo Titi, ZA (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Backgrounds: Amino acid cysteine is one of the amino acids that can help the process of accelerating growth. In the process of growth of amino acids cysteine has a role in accelerating the transcription of hormone receptors on the reaction of zinc finger protein (ZFP), induction of Transforming Growth Factor Î² (TGF Î²) and the formation of Cystein Rich Intestinal ProteinCRIP) that strongly linked advanced metabolic reactions. Urine is one of the final results of the metabolic process and can describe the metabolic status subjectively.Methods: Research with pre-post randomizet control design has been done with a large sample of 2 x 15 samples divided into treatment and control group. In the treatment group was given cysteine amino acid as much as 25 mg / day with time of administration for 3 months or 90 times giving.Â Results: The results showed that amino acid administration of cysteine could not improve metabolic disorder in stunting children with indicator of urinalysis result. In this research, we get the description of energy intake that has not reached AKG. This study also provides an illustration of the low TB addition in all study groups. Anthropometric changes in both BB and TB have significant changes in both treatment and control groups.Keywords: Stunting, Amino acids cysteine, urinalysis, energy intake, Weight Loss, Height